The Influence of Organizational Culture and Compensation on Employee Performance with Work Motivation as an Intervening Variable at PT XYZ - Faradhillah, Ruri; Haryoto, Cecep Yoto (Jurnal EMT KITA, 2025)
With work motivation acting as an intervening variable, this study attempts to evaluate and examine the effects of organizational culture and compensation on employee performance at PT XYZ. The dependent variables are employee performance and work motivation, whereas the independent variables are organizational culture and compensation. The research employed a data gathering strategy that involved delivering questionnaires to 165 workers of PT XYZ. Using primary data, the study methodology is quantitative and associative in character. and Structurally Equitional Modeling (SEM) with PLS 4 is the data analysis model utilized.The findings of this study demonstrate that, with a coefficient value of 0.364, organizational culture has a positive and significant impact on employee performance; compensation positively and significantly affects employee performance with a coefficient value of 0.247; organizational culture positively and significantly affects employee performance through work motivation with a coefficient value of 0.155; and compensation positively and significantly affects employee performance through work motivation with a coefficient value of 0.140. Employee performance is positively and significantly impacted by work motivation, as indicated by the coefficient value of 0.354.